Electron energy deposition in molecular hydrogen gas: a Monte Carlo simulation using convergent close-coupling cross sections. (9th November 2021) - Horton, Reese K; Scarlett, Liam H; Zammit, Mark C; Bray, Igor; Fursa, Dmitry V
Abstract: A Monte Carlo simulation of electron energy deposition in a gas of molecular hydrogen has been conducted with the aim of producing an ab initio estimate of energy deposition parameters such as the mean energy per ion pair. A set of cross sections obtained using the molecular convergent close-coupling method were used as input. At high incident electron energies the mean energy per ion pair was calculated to be 36.3 eV, agreeing with the recommended value of 36.5 ± 0.3 eV. This represents the first fully ab initio calculation of the mean energy per ion pair using a self consistent data set.